Meme as a Tool for Resistance Towards Hustle Culture: A Critical Discourse Analysis: The Case Study of @ecommurz - Nadia Farah Lutfiputri (ULTIMA Comm, 2022)
There is currently an emergence of Indonesian meme accounts on Instagram which specifically discuss the work culture in startups or technology-based companies. One of the most popular is @ecommurz, which has roughly 152,000 followers (by 12 July 2022). Using Fairclough's critical discourse analysis, this study aims to analyze how the working class group use memes from the @ecommurz Instagram account to demonstrate a resistance to hustle culture in Indonesia, particularly in startup environments. This study shows that Ecommurz has demonstrated the potential of meme accounts as a platform that unites middle-class workers to carry out resistance to the hegemony of the dominant culture by drawing on Gramsci's (1971) conceptions of cultural hegemony and resistance. Ecommurz has democratized the discussion of issues and difficulties encountered by many middle-class workers in the workplace through humorous and casual memes. Furthermore, it has also increased public awareness of workers' rights and prompted real systemic change.